OPTIMALISASI GERAKAN NASIONAL SADAR TERTIB ARSIP (GNSTA) PADA DINAS PERPUSTAKAAN DAN KEARSIPAN KABUPATEN SLEMAN DALAM MENDUKUNG PELAKSANAAN REFORMASI BIROKRASI - Herawati Dian Elvandari; Sugiyanto Sugiyanto (Jurnal Inovasi Penelitian, 2023)
Archive affairs in governance have a very important role, good records management is a reflection of the implementation of good governance. Archives cannot be separated from bureaucratic reform, the quality of archives management is one of the indicators for evaluating the implementation of bureaucratic reform in the area of change in governance arrangements. But unfortunately so far archive affairs in Indonesia are still underestimated and have not received great attention in the process of administering government. This prompted the National Archives of the Republic of Indonesia (ANRI) to launch the National Archives Awareness Movement (GNSTA) as an effort to increase awareness of the importance of archives and archive management. Through this research, the authors try to describe how the GNSTA optimization in the Sleman Regency Library and Archives Service supports the implementation of bureaucratic reform. The method used in this research is descriptive qualitative method. The results showed that the optimization of GNSTA by the Library and Archives Service of Sleman Regency had been carried out well, but it still needed to be optimized to support the implementation of bureaucratic reform. Awareness of the importance of archives must be increased in order to create an awareness culture of orderly records in government administration so that it will support the implementation of bureaucratic reform and create good governance